Neurosurgical Issues in Pregnancy - Can, Anil; Du, Rose (Seminars in Neurology, 2017)
Although rare, intracranial hemorrhage due to rupture of cerebral vascular malformations or intracranial aneurysms during pregnancy is a potentially devastating and life-threatening disorder, posing a diagnostic and therapeutic challenge to a multidisciplinary team of neurosurgeons, neurologists, obstetricians, and anesthesiologists. Despite the significant risk of morbidity and mortality affecting both the mother and the unborn child, knowledge of the natural history, epidemiology, and appropriate management of cerebral vascular malformations and intracranial aneurysms in pregnant women is limited. Although emergent neurosurgical concerns usually outweigh obstetric considerations, and treatment of these disorders is generally similar in pregnant and nonpregnant women, any necessary and feasible modifications to protect the unborn child should be made. This article reviews the management of ruptured intracranial aneurysms and cerebral vascular malformations, including arteriovenous malformations, cavernous malformations, and moyamoya disease, in women during pregnancy, partus, and puerperium.
Keywords: arteriovenous malformation; moyamoya disease; aneurysm; cavernous malformation; pregnancy